CHANGES IN FIRST-TIME TRAVELLERS’ MOTIVATIONS FOR SHARED ACCOMMODATIONS: INSIGHTS FROM SELF-DETERMINATION THEORY - Lei Qin (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
In recent years, more and more travellers have chosen shared accommodations as their tourism accommodations, and their initial motivations tend to be different from their motivations after participation. However, beyond anecdotal evidence, there is a dearth of understanding of changes in motivations for first-time travellers. Therefore, this study aims to investigate how first-time shared accommodation travellers change over time (hereafter referred to as first-time travellers) by employing Self-Determination theory (SDT) as the theoretical foundation. The data was collected with the purposive sampling approach from 30 first-time travellers’ interviews, before and after their first experience of shared accommodations. The results indicate that changes in first-time travellers’ basic needs are found to internalize or externalize their motivations in repeat participation. This study adds to the literature on the dynamic motivation process for first-time travellers, identifies the underlying reasons behind the motivational changes, and provides marketing strategies for shared accommodation practitioners to target and attract this group of travellers to use shared properties repeatedly.